Pro-apoptotic and anti-cancer properties of diosgenin: A comprehensive and critical review - Sethi, G.; Shanmugam, M.; Warrier, S.; Merarchi, M.; Arfuso, Frank; Kumar, A.; Bishayee, A. (MDPI Publishing, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Novel and alternative options are being adopted to combat the initiation and progression of human cancers. One of the approaches is the use of molecules isolated from traditional medicinal herbs, edible dietary plants and seeds that play a pivotal role in the prevention/treatment of cancer, either alone or in combination with existing chemotherapeutic agents. Compounds that modulate these oncogenic processes are potential candidates for cancer therapy and may eventually make it to clinical applications. Diosgenin is a naturally occurring steroidal sapogenin and is one of the major bioactive compounds found in dietary fenugreek (Trigonella foenum-graecum) seeds. In addition to being a lactation aid, diosgenin has been shown to be hypocholesterolemic, gastro-and hepato-protective, anti-oxidant, anti-inflammatory, anti-diabetic, and anti-cancer. Diosgenin has a unique structural similarity to estrogen. Several preclinical studies have reported on the pro-apoptotic and anti-cancer properties of diosgenin against a variety of cancers, both in in vitro and in vivo. Diosgenin has also been reported to reverse multi-drug resistance in cancer cells and sensitize cancer cells to standard chemotherapy. Remarkably, diosgenin has also been reported to be used by pharmaceutical companies to synthesize steroidal drugs. Several novel diosgenin analogs and nano-formulations have been synthesized with improved anti-cancer efficacy and pharmacokinetic profile. In this review we discuss in detail the multifaceted anti-cancer properties of diosgenin that have found application in pharmaceutical, functional food, and cosmetic industries; and the various intracellular molecular targets modulated by diosgenin that abrogate the oncogenic process.